Elaboração e validação de um instrumento de registro de feridas crônicas - MELO, Adriana Feliciana (2015)
Chronic wounds are complex and involve an individualized assessment. To follow the evolution process of these wounds, the records should be systematized, providing a global view, identify risks and maximize communication. The objectives of this study were to develop an assessment tool and evolution of chronic wounds and verify its psychometric properties. It is a methodological research, developed in three stages: stage I, development of the instrument, called chronic wounds recording instrument; stage II, characterized by apparent and content validation; and stage III, to verify the validity and reliability of the instrument. At this stage, we used a strategy of inter-rater reliability. To test the reliability of the instrument the items were used simple weighted Kappa and the general scores on the observations of the researchers, the interclass correlation coefficient (ICC), which was 0.914, and to check the validity of the instrument discretion, the correlation coefficient of Pearson, with result of 0.573. The instrument was administered to 71 patients with chronic wounds, from October 2014 to January 2015, in inpatient units of internal medicine and surgery at the Clinic and the Clinical Hospital of the Federal University of Triângulo Mineiro. In the sample, 56.3% were women, 72% elderly, and 60.6% had cardiovascular disease. In the etiology of wounds evaluated the highest percentage were pressure ulcers, with 45.1%. Most of the agreements of the instrument items was classified as moderate and substantial, being found in items that described the necrotic tissue type (k = 0.754), type of exudate (k = 0.630), and pain in subparagraphs (k = 0.683 ), odor (k = 0.800), edema (k = 0.613). The results show that the instrument of this study is valid and reliable. The instrument is suggested that applied in longitudinal studies and in larger populations, with equal distribution of different etiologies chronic ulcers, in order to contribute to improving the quality of care, with proper documentation support, allowing orientation for the treatment and continuity of care.